The Tudors : History of a Dynasty. - Loades, David (Bloomsbury Publishing PLC, 2012)
"This book is about one of the most powerful and influential dynasties in English history, a dynasty of five monarchs who ruled their domain for over a century. The Tudors were concerned with building a government that would endure, hence their constant concern with succession, an anxiety which lasted throughout the century. Although all Tudor monarchs believed that their authority derived from God, they had different ways of expressing that conviction, and above all they believed in ruling with consent and advice. For this reason they built partnerships, not with the old nobility as their predecessors had done, but with the wider community of the gentry, and above all with parliament. These partnerships with the church and state lasted for centuries and still influence British politics today."--Bloomsbury Publishing.